2014
DOI: 10.1186/1741-7015-12-95
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in child mortality in ten major African cities

Abstract: BackgroundThe existence of socio-economic inequalities in child mortality is well documented. African cities grow faster than cities in most other regions of the world; and inequalities in African cities are thought to be particularly large. Revealing health-related inequalities is essential in order for governments to be able to act against them. This study aimed to systematically compare inequalities in child mortality across 10 major African cities (Cairo, Lagos, Kinshasa, Luanda, Abidjan, Dar es Salaam, Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 49 publications
1
32
0
2
Order By: Relevance
“…The opposite was true for conflict countries; this is in line with a study on breast feeding in violent conflict situations in Iraq which found that breastfeeding incidence reduced as casualties from armed conflict rose 34. This finding could be explained by the reduced health staff,11 25 35 user fees,6 25 36 and geographical barriers25 arising from conflict, as many women are counselled in breastfeeding practices,34 37 and support from health professionals has been found to be a key determinant of breast feeding 34. Alternately, mothers in conflict countries who have been displaced could have impaired nutritional intake, thus reducing breastmilk quality and a decline in breast feeding.…”
Section: Discussionsupporting
confidence: 73%
“…The opposite was true for conflict countries; this is in line with a study on breast feeding in violent conflict situations in Iraq which found that breastfeeding incidence reduced as casualties from armed conflict rose 34. This finding could be explained by the reduced health staff,11 25 35 user fees,6 25 36 and geographical barriers25 arising from conflict, as many women are counselled in breastfeeding practices,34 37 and support from health professionals has been found to be a key determinant of breast feeding 34. Alternately, mothers in conflict countries who have been displaced could have impaired nutritional intake, thus reducing breastmilk quality and a decline in breast feeding.…”
Section: Discussionsupporting
confidence: 73%
“…The comparable rates for post-neonatal mortality (one month to one year) in low versus high SDI countries, were 23.2 and 1.4 deaths per 1,000 live births, and among children aged between one and five years, 24.4 and 0.8 deaths per 1,000 live births, respectively [2]. A study which systematically compared household wealth inequalities in child mortality in 10 African cities between 2000, 2007 and 2011 showed wide disparities across time and place [7].…”
Section: Introductionmentioning
confidence: 99%
“… 3 5 Such disparities in uptake of health services lead to the continuing problem of high child mortality especially among the poorest. 6 …”
Section: Introductionmentioning
confidence: 99%